A comparative study to assess I-gel as an alternative to endotracheal tube in laparoscopic surgeries - Quraishi, Athar Un Nisa; Goel, Akshi; Quraishi, Kamran Ahmad; Ul Ayoub, Touseef (International Journal of Research in Medical Sciences, 2023)
Background: This study was conducted to compare and evaluate the effectiveness of I-gel over endotracheal tube with regards to respiratory and hemodynamic parameters in laproscopic surgeries. Methods: In this study 60 adult patients of either sex, of ASA status I or II, aged 16 to 60 years, undergoing laparoscopic surgeries under general anesthesia were randomly studied. In Group-A (I-gel) appropriate sized I-gel was inserted, and in Group-B (ETT) patient’s airway was secured with laryngoscopy-guided endotracheal intubation. Monitoring of PR, MBP, SpO2 and EtCO2 was done throughout the peri-operative period. Haemodynamic and ventilatory parameters were recorded before induction (baseline), just after intubation, then at 1, 3 and 5 min after I-gel insertion/intubation, after pneumoperitoneum, after change of position, before and 5 min after release of pneumoperitoneum and after I-gel removal/extubation. Results: Following the insertion of airway device there was significant rise in PR (3 min after intubation [P = 0.011, df-58, CI-95%]) and MBP (3 min after intubation [P = 0.02, df-58, CI-95%], 5 min after intubation [P = 0.04, df-58, CI-95%]) in Group-B patients when compared to Group-A patients. Following insertion of airway device there was no significant difference in EtCO2 (3 min after intubation [P = 0.778, df-58, CI-95%]), 5 min after intubation [P = 0.75, df-58, CI-95%]) in Group-B patients when compared to Group-A patients. Conclusions: I-gel requires less time for insertion with minimal haemodynamic changes when compared to ETT. I-gel can be a safe and suitable alternative to ETT for laparoscopic surgery.